Botulinum toxin treatment for hyperlacrimation secondary to aberrant regenerated seventh nerve palsy or salivary gland transplantation. Issue 1 (1st January 2002) - Keegan, David J; Geerling, Gerd; Lee, John P; Blake, Glen; Collin, J Richard; Plant, Gordon T
Abstract : Aim: To investigate the potential of botulinum toxin A for treating hyperlacrimation. Methods: Three patients with unilateral symptoms of hyperlacrimation (diagnosed as "crocodile tearing") and one patient with a submandibular salivary gland transplant (SMGT) were studied. Tear production was quantified in the resting and stimulated (chewing or following exercise) state, using Schirmer's test and tear clearance. Lacrimal scintigraphy was used to assess outflow. Intraglandular injections (for patients with "crocodile tears") or periglandular injections (for the SMGT patient) of Dysport were administered in divided doses. Results: Two of the three eyes with reported gustatory lacrimation had a higher Schirmer test result than their fellow eye following gustatory stimulation. Scintigraphy, with and without stimulation, confirmed a patent drainage system in these patients. The other patient demonstrated a functional obstruction to tear flow. After treatment patients with confirmed gustatory lacrimation and the SMGT patient had a marked reduction in tearing at 2 weeks. This effect lasted 3–4 months. There was no demonstrable improvement in the patient with epiphora secondary to functional obstruction. Two patients who had received intraglandular injections developed a ptosis, which resolved spontaneously. Conclusions: This study illustrates that gustatory lacrimation is a difficult diagnosis. In post-facial nerve palsy a functional element must always be considered. However, in confirmed hyperlacrimation botulinum toxin treatment is effective but side effects may occur.